THE RELATIONSHIP OF KNOWLEDGE, ATTITUDE AND FAMILY SUPPORT WITH THE NUTRITIONAL STATUS OF THE ELDERLY: LITERATURE REVIEW - Ambrosia Barek, Maria; Haryanto, Joni; Ulfiana, Elida (Universitas Airlangga, 2021)
Introduction: Elderly are individuals who are vulnerable and at risk of experiencing health problems related to nutritional status. Families who live together are expected to be able to provide nutritional intake in accordance with the condition of the elderly so that adequate knowledge is needed in preparing the need for balanced nutrition. The purpose of this study was to analyze the relationship between knowledge, attitudes, and family support to elderly's nutritional status. Methods: The search for literature review articles was carried out in four databases (Scopus, Science Direct, Pub med, and Google Scholar) with a publication span of 2016-2020. The prism checklist was used to guide this review. Analysis and data tabulation were carried out in the article. Title, abstract, full text and methodology were assessed to determine study eligibility. Results: A total of 10 studies matched the inclusion criteria of the study, consisting of 6 cross-sectional studies and 4 qualitative studies. A review study found that good knowledge, positive attitude and good family support are directly proportional to the nutritional status of the elderly. Discussion: Family has a role in maintaining the health of the elderly, one of which is in fulfilling nutrition. Knowledge, attitudes and family support are related to the nutritional status of the elderly. Conclusions: Families who have knowledge related to nutrition can provide complete food intake and according to the needs of the elderly. A good family attitude will increase their support in helping fulfill nutrition.